EFFECT OF URTICA DIOICA AND CAMELLIA SINENSIS ON ROOSTER REPRODUCTIVE AND TESTICULAR TRAITS - Emad Abdel-Jabbar Ali , Emad Abdel-Jabbar Ali; Ali Sabah Al-Hassani , Ali Sabah Al-Hassani; Nihad Abdel-Latif Ali , Nihad Abdel-Latif Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to investigate the effects of varying dosages of Urtica dioica (nettle) leaf powder and Camellia sinensis (white tea) powder on the reproductive and histological characteristics of rooster testes. Conducted at the College of Agriculture, Al-Qasim Green University, over a 42-day period, the experiment involved 21 roosters at 45 weeks of age, which were randomly assigned to seven treatment groups with three replicates each. The treatment groups included: a standard diet without any additives as the control; a standard diet supplemented with 100 mg/kg or 150 mg/kg of white tea powder; a standard diet supplemented with 100 mg/kg, 150 mg/kg, or 200 mg/kg of nettle leaf powder. The results demonstrated significant improvements in sperm concentration, osmotic resistance, ejaculate volume, and individual sperm motility in certain groups receiving white tea and nettle leaf powders.